Diversity and conservation of bats from Loreto, Peru - Graham-Angeles, Laura (2021)
In this work, an updated list of species of bats from Loreto is presented, this was elaborated using information of databases, zoological collections, and specialized literature. The results confirm Loreto as the most diverse department of Peru with 114 species of bats grouped into 7 families (19.9% of the Peruvian mastofauna), which include two of the nine endemic species to Peru: Micronycteris (Micronycteris) matses and Hsunycteris dashe. Additionally, 444 different locations were found with specimen records, located mainly along rivers. Species recorded in four or less different locations are considered rare, while species recorded in 111 or more different locations are considered common. We present a map of the Loreto ecoregions with the different localities, both historical and contemporary, as well as a map of density of locations per 25 km2, which identifies 6 areas of information gaps: 1) North and middle Putumayo, 2) Northwest Maynas and northeast Loreto, 3) Middle Maynas, 4) North-middle Datem del Marañón, north Alto Amazonas and western end of Loreto, 5) South-middle Requena and eastern end of Ucayali and 6) Western end of Ucayali. Finally we present distribution maps for each species reported here for Loreto.